The Scope of Internal Marketing: Defining The Distinction Between Human Resource Management and Marketing: Evidence From Public Banks in Erbil/Iraq - Saeed Ahmad, Aram Tahir; Mohammed, Aso Rahman; Mahmood Salman , Peshraw; Othman, Bestoon (JBS Nexus, 2026)
A strategic management technique that connects marketing and human resource management (HRM) with internal marketing encourages employee involvement to boost organizational performance. The use of internal marketing is still not well understood in the context of public banks in Erbil, Iraq, where bureaucratic obstacles and issues regarding customer service quality continue to exist. While separating internal marketing from conventional HRM methods, this study explores the scope of internal marketing by examining how its essential elements internal communication, employee motivation, leadership support, and training affect organizational performance and customer satisfaction. The study used structured questionnaires to collect data from 200 employees of five main public banks in Erbil, using a quantitative research approach. The results show a strong correlation between internal marketing strategies and enhanced customer orientation, employee happiness, and service delivery, suggesting that internal marketing is a strategic organizational approach rather than just an HR function. This study adds to the theoretical conversation by creating a conceptual framework that distinguishes internal marketing from HRM and provides useful advice for public banking organizations. The limitations, implications, and suggestions for further study are also discussed.